KEINGINAN UNTUK BERTAHAN ATAU KELUAR DARI ORGANISASI DI UNIT BISNIS UMY - Astuti, Isthofaina (Jurnal Manajemen Bisnis, 2019)
In an effort to improve the professionalism of Micro, Small and Medium Enterprises in managing their business, each leader of Micro, Small and Medium Enterprises must be able to predict the desire of Micro, Small and Medium Enterprises to leave the organization (turnover intention). Turnover intention will have an impact on human resource management and further impact on the ability of organizations to compete with other organizations.The high level of willingness to move in MSMEs is one of the factors reported by several previous studies as HR problems that affect the success of MSMEs.The factors referred to by previous studies as factors that are able to predict turnover intention are job satisfaction and organizational commitment. So, the aim of the research is to examine the effect of job satisfaction as an antecedent variable on organizational commitment to turnover intention, with organizational commitment as an intervening variable.In this research, some instruments were used: Mienisotta Satisfaction Questionnaire (MSQ) to measure job satisfaction, Allen and Mayer (1990) to measure organizational commitment, and Hom and Griffieth (1991) to measure turnover intention. Path Analysis wa used to analyze the data.The results showed that job satisfaction is an antecedent variable of organizational commitment, but not an antecedent variable of turnover intention. Whereas, organizational commitment is not an intervening variable for the correlation between job satisfaction and turnover intention.